Síntese e caracterização de óxidos de cério e cobalto obtidos por gel-combustão e Pechini aplicados às reações de oxidação de n-hexano - Sales, Luciano Leal de Morais (2008)
Oxide type spinel AB2O4 presents structure adjusted for application in the automobile industry. The spinel of cobalt has many practical applications had its excellent physical and chemical properties such as catalyst in hydrocarbon oxidation reaction. The CeO2 has been used in many of these processes because it assigns to a material with excellent thermal resistance and mechanics, high capacity of oxygen stockage (OSC) among others properties. This work deals with the synthesis, characterization and catalytic application of spinel of cobalt and CeO2 with fluorita structure, obtained for method of Pechini and method of Gel-Combustion. The process of Pechini, the puff was obtained at 300 ºC for 2 h in air. In the process of Gel-Combustion the approximately at 350 ºC material was prepared and burnt for Pyrolysis, both had been calcined at 500 ºC, 700 ºC, 900 ºC and 1050 ºC for 2 h in air. The materials of the calcinations had been characterized by TG/DTA, electronic microscopy of sweepings (MEV), spectroscopy of absorption in the infra-red ray (FTIR) and diffraction of X-rays (DRX). The obtained material reaches the phase oxide at 450 oC for Pechini method and 500 °C for combustion method. The samples were submitted catalytic reaction of n-hexane on superficies of materials. The reactor function in molar ration of 0, 85 mol.h-1.g-1 and temperature of system was 450 °C. The sample obtained for Pechini and support in alumine of superficial area of 178,63 m2.g-1 calcined at 700 ºC, give results of catalytic conversions of 39 % and the sample obtained for method of gel-combustion and support in alumina of 150 mesh calcined at 500 ºC result 13 % of conversion. Both method were selective specie C1